Analysis of Body Weight of Kacang Goats in the Soropia Subdistrict, Konawe Regency - Lois Jasriani R.B; Farra Sasmita; Awal Maulid Sari; Inal Inal; Hajar Hajar; Natsir Sandiah (Fakultas Teknologi Pertanian Unsultra, 2026)
This study aims to analyze the body weight characteristics of Kacang goats based on sex and to determine the level of body weight variation in Kacang goats in Soropia Subdistrict, Konawe Regency. The study was conducted from September to October 2025 using a quantitative approach with a descriptive-analytical method. The study sample consisted of 74 male and female Kacang goats ranging in age from 6 months to over 24 months. Data collection was performed through direct body weight measurements using a digital scale with a precision of 0.1 kg. Data analysis was performed descriptively to obtain the mean, standard deviation, and coefficient of variation, while differences in body weight between male and female goats were analyzed using a t-test with the assistance of SPSS version 20. The results of the study showed that the average body weight of male Kacang goats was 16.41 ± 1.31 kg with a coefficient of variation of 7.97%, while female Kacang goats had an average body weight of 15.89 ± 1.19 kg with a coefficient of variation of 7.46%. Statistical test results indicate a significant difference (P<0.05) between the body weights of male and female Kacang goats. Male goats tend to have higher body weights compared to female goats due to physiological and hormonal factors, particularly testosterone, which supports muscle and body growth. The low coefficient of variation indicates that the Kacang goat population exhibits a fairly high level of growth uniformity. This study concludes that sex has a significant effect on the body weight of Kacang goats in Soropia Subdistrict and that the livestock population exhibits relatively homogeneous growth characteristics.